Sosialisasi Budidaya Lele Terpal dan Vertikultur Sayuran serta Praktik Pembuatan Pakan di Desa Banyuroto, Kabupaten Magelang - Rusdjijati, Retno; Permadi, Jefri; Pujiarto, Bambang (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
In order to help the residents of Kenayan Hamlet, Banyuroto Village, Sawangan District, Magelang Regency in controlling the high stunting rate of 29,06 percent, the implementation team and students from Muhammadiyah University conducted community service activities through the Community Empowerment by Students (PMM) scheme. One of the methods used was by holding a socialization of catfish cultivation in tarpaulins integrated with vertical vegetable cultivation, and the practice of making catfish feed to target partners, namely the Melati Women Farmers Group (KWT) and the Sabilurrohman Mosque Youth Group. The activity aims to increase the availability of family food with balanced nutrition and as a means for entrepreneurship. The activity, attended by 20 participants, resulted in an increase in understanding of catfish cultivation in tarpaulin and vegetable cultivation in vertical cultivation by 98 percent from the previous 67 percent.